Genetic Analysis of KRT9 Gene Revealed Previously Known Mutations and Genotype-Phenotype Correlations in Epidermolytic Palmoplantar Keratoderma - Li, Yuwei; Tang, Lili; Han, Yang; Zheng, Liyun; Zhen, Qi; Yang, Sen; Gao, Min (Frontiers in Genetics, 2019)
Epidermolytic palmoplantar keratoderma (EPPK, OMIM 144200) is an autosomal dominant inherited disease, clinically characterized by diffuse yellowish thickening of the skin on the palms and soles, usually with erythematous borders during the first weeks or months after birth. It caused by mutations in the keratin gene (KRT9). Domestic and foreign scholars have discovered 33 KRT9 gene mutations in 100 EPPK families, of which 23 mutations are located in the 1A region (a mutation hot spot region), 7 are located in the 2B region, and the remaining 3 are synonymous mutations. In this study, three heterozygous mutations (p.N161S, p.R163W and p.R163Q), located in regions of the gene encoding the conserved central a-helix rod domain, were detected in the KRT9 gene of the three large Chinese families. This study found that codon 163 (48 of 100 cases) is indeed a hot spot mutation site for KRT9, and the mutations of EPPK, combined with the occurrence of knuckle pads (15 of 100 cases), are p.N161S (4%), p. R163W (4%), p.L168S (3%), p.M157T (1%), p.L160F (1%), p.C406R (1%) and p.L458p (1%). This study found that hot spot mutations for which EPPK is associated with knuckle pads may be p.N161S and P.R163W, and the hot spot mutation of EPPK not occurring in combination with knuckle pads is p.R163Q (15 of 100 cases), which should help lay the foundation for genetics counselling, prenatal diagnosis and clinical treatment of EPPK.